Generative Patterns for Designing Multiple User Interfaces - Nguyen, Thanh-Diane; Vanderdonckt, Jean; Seffah, Ahmed (2016 IEEE/ACM International Conference on Mobile Software Engineering and Systems (MOBILESoft), 2016)
End users interacting with mobile services through a wide diversity of mobile devices and platforms inevitably endure various user experiences when no consistency is ensured across these devices and platforms. Developing the same service for heterogeneous devices remains a challenging task: how to ensure that the service will provide end users with the same level of user experience or at least a common minimum level of usability across software devel-opment and deployment platforms. This paper addresses this problem by introducing a generative design pattern-based approach for cross-device services: a design pattern captures frequent interactive behaviors at a higher level of abstraction than the code level, the selection of such a design pattern is then subject to parametrization so as to drive a code generation process. The pattern is not only considered descriptive, since it specifies a consistent user experience across devices, but also generative because it ensures some consistency across different devices and platforms since the pattern is instantiated in the same way for each device or platform. To exemplify this process, the master-details design pattern is detailed and illustrated on a case study for a car rental mobile service. A pilot study conducted with thirty-two participants suggests that this is a viable approach for quickly producing multi-devices services, with limited development effort, but also with limited variability.